Prevalence and significance of T-wave inversion in Arab and Black paediatric athletes: Should anterior T-wave inversion interpretation be governed by biological or chronological age?. (29th August 2020) - McClean, Gavin; Riding, Nathan R; Pieles, Guido; Sharma, Sanjay; Watt, Victoria; Adamuz, Carmen; Johnson, Amanda; Tramullas, Antonio; George, Keith P; Oxborough, David; Wilson, Mathew G
Abstract: Background: International electrocardiographic (ECG) recommendations regard anterior T-wave inversion (ATWI) in athletes under 16 years to be normal. Design: The aim of this study was to identify the prevalence, distribution and determinants of TWI by ethnicity, chronological and biological age within paediatric athletes. A second aim was to establish the diagnostic accuracy of international ECG recommendations against refinement within athletes who present with ECG variants isolated to ATWI (V1 –V4 ) using receiver operator curve analysis. Clinical context was calculated using Bayesian analysis. Methods: Four hundred and eighteen Arab and 314 black male athletes (11–18 years) were evaluated by ECG, echocardiogram and biological age (by radiological X-ray) assessment. Results: A total of 116 (15.8%) athletes presented with ATWI (V1 –V4 ), of which 96 (82.8%) were observed in the absence of other ECG findings considered to be abnormal as per international recommendations for ECG interpretation in athletes; 91 (12.4%) athletes presented with ATWI confined to V1 –V3, with prevalence predicted by black ethnicity (odds ratio (OR) 2.2, 95% confidence interval (CI) 1.3–3.5) and biological age under 16 years (OR 2.0, 95% CI 1.2–3.3). Of the 96 with ATWI (V1 –V4 ) observed in the absence of other ECG findings considered to be abnormal, as per international recommendations for ECG interpretation in athletes, diagnostic accuracy was 'fail' (OR 0.47, 95% CI 0.00–1.00) for international recommendations and 'excellent' (OR 0.97, 95% CI 0.92–1.00) when governed by biological age under 16 years, providing a positive and negative likelihood ratio of 15.8 (95% CI 1.8–28.1) and 0.0 (95% CI 0.0–0.8), respectively. Conclusion: Interpretation of ECG variants isolated with ATWI (V1 –V4 ) using international recommendations (chronological age <16 years) warrants caution, but governance by biological age yielded an 'excellent' diagnostic accuracy. In the clinical context, the 'chance' of detecting cardiac pathology within a paediatric male athlete presenting with ATWI in the absence of other ECG findings considered to be abnormal, as per international recommendations for ECG interpretation in athletes (positive likelihood ratio 15.8), was 14.4%, whereas a negative ECG (negative likelihood ratio 0.0) was 0%.